Recent advances and trends in the applications of nanomaterials in optical sensing platforms - Jampasa, Sakda; Khamcharoen, Wisarut; Wirojsaengthong, Supacha; Suea-Ngam, Akkapol; Traipop, Surinya; Ozer, Tugba; Unob, Fuangfa; Puthongkham, Pumidech; Chailapakul, Orawon (ELSEVIER SCI LTD, 2024)
Optical sensors have been developed to detect important markers in various applications such as food, health, and environment. Nanomaterials have been designed and integrated in them to be desirable optical sensors, exhibiting improved analytical performance from their distinct physicochemical properties. This review summarizes the designs, integrations, and applications of nanomaterials such as carbon-based materials, metallic nanoparticles, polymers, and nanostructures such as nanozyme and polymeric nanostructures, to enhance the performance of optical sensors. Optical sensors based on colorimetry, photoluminescence including fluorescence and near-infrared spectroscopy, surface-enhanced raman spectroscopy and surface plasmon resonance spanned through many applications will be covered. Future perspectives of developing optical sensors using greener approaches, multiplexed detection, and applications of machine learning will also be given. Bridging the sciences and arts of nanomaterial design and synthesis with the optical properties of materials and matters enables the improvement of optical sensors for good health and well-being.
Keywords: Optical sensors; Food monitoring; Environmental monitoring; Clinical monitoring; Nanomaterials; SURFACE-PLASMON RESONANCE; HYBRIDIZATION CHAIN-REACTION; COLORIMETRIC DETECTION; SILVER NANOPARTICLES; SIGNAL AMPLIFICATION; IMPRINTED POLYMER; FLUORESCENT-PROBE; GRAPHENE OXIDE; SENSORS; ENVIRONMENT; Chemistry